Manuel Pedro Ferreira, ​Revisiting the Music of Medieval France. From Gallican to Dufay ​(Farnham - Burlington, Ashgate Variorum, 2012) - Boudeau, Océane (Revista Portuguesa de Musicologia, 2018)
Recension : Manuel Pedro Ferreira, Revisiting the Music of Medieval France. From Gallican to Dufay (Farnham - Burlington, Ashgate Variorum, 2012)